Diagnostic values of MMP-7, MMP-9, MMP-11, TIMP-1, TIMP-2, CEA, and CA19-9 in patients with colorectal cancer. Issue 5 (May 2021) - Huang, Xiwen; Lan, Yongquan; Li, En; Li, Jiaquan; Deng, Qiaoting; Deng, Xunwei
Objective: Colorectal cancer (CRC) is one of the most common and lethal malignancies. The identification of precise and noninvasive biomarkers is urgently needed to aid the early diagnosis and clinical management of CRC. Methods: A total of 112 patients with CRC and 115 healthy control subjects were included in this study. Serum levels of matrix metalloproteinase (MMP)-7, MMP-9, MMP-11, tissue inhibitor of metalloproteinase (TIMP)-1, and TIMP-2 were analyzed by enzyme-linked immunosorbent assay, and carcinoembryonic antigen (CEA) and carbohydrate antigen (CA)19-9 levels were measured using an automatic immunoassay analyzer. Results: MMP-7, MMP-9, MMP-11, TIMP-1, TIMP-2, CEA, and CA19-9 levels were all significantly higher in CRC patients compared with healthy controls. MMP-7, TIMP-1, and CEA levels were also closely related to clinicopathologic features in patients with CRC. The combination of serum CEA, MMP-7, and TIMP-1 significantly improved the diagnostic value compared with any single marker (area under the curve 0.858–0.890). Furthermore, a combined detection model including MMP-7, TIMP-1, and CEA improved both the specificity and sensitivity for detecting CRC. Conclusions: The results showed that combined detection of CEA, MMP-7, and TIMP-1 in serum could provide a specific and sensitive biomarker for the diagnosis of CRC.